Implementing a Gender Transformative Approach in Community-Based Breeding Programs (CBBP) and Sheep Fattening Cooperatives - Nemera Woyessa, Martha; Tsige, Meseret; Najjar, Dina; Alma, Eileen (International Center for Agricultural Research in the Dry Areas, 2025)
ICARDA, in partnership with WE-Action Ethiopia, has implemented a Gender Transformative Approach (GTA) in Southern Ethiopia to address restrictive gender norms limiting women’s participation and leadership in Community-Based Breeding Programs (CBBP) and sheep fattening cooperatives. A gender and social inclusion analysis in Doyogena district identified six key barriers, including unequal roles in livestock marketing, decision-making, labor, and widespread gender-based violence and discrimination. From April 2023 to March 2025, the GTA used the four-phase SASA methodology—Start, Awareness, Support, and Action—to spark behavioral change. Through trained support staff, Positive Deviants (PDs), and Community Activists (CAs), the initiative engaged cooperatives, religious and traditional associations, households, and local institutions in norm-challenging dialogues. The GTA directly reached 8,592 individuals (60% women) and indirectly impacted 42,960 community members through local radio programming and institutional partnerships. These efforts broadened awareness and improved access to gender-responsive services. As a result, 35.1% of women and 25% of men who participated rejected the belief that men should control livestock sales—compared to only 14.7% of non-participating women and 12.8% of non-participating men. GTA has transformed cooperatives into spaces for gender dialogue and equity, offering a scalable model for inclusive, community-driven transformation in rural livelihoods.